FRI0680 Tetherin, a novel type i interferon biomarker on blood leucocytes can capture interferon status and correlates with ustekinumab (STELARA) therapy response in psoriatic disease. (12th June 2018) - El-Sherbiny, Y. M.; Savage, L.; Alase, A.; Vital, E.; Wittmann, M.; Emery, P.; McGonagle, D.
Abstract : Background: Recently Ustekinumab, an IL12/23 p40 monoclonal antibody that is licensed for Psoriatic Arthritis and Psoriasis, showed promising results in phase II trials in SLE- a prototype IFN mediated disease. We previously confirmed a novel IFN gene scoring system associated with the different SLE symptoms (manuscript in review). Additionally, we also recently validated in two independent cohorts the value of BST2/ tetherin as IFN-I biomarker assay correlates with clinical activity and predicts clinical flare in SLE. Given that psoriasis has several SNPs in the IFN pathway; Thus mechanistic studies of the effect of Ustekinumab on the IFN pathway can be explored in this disease setting. Objectives: This work tested the hypothesis that a novel interferon type I (IFN-I) status markers in the blood and skin of Ustekinumab treated psoriasis patients might correlate with therapy responses and provide insights into how p40 blockers may affect IFN pathways in a relevant human disease model. Methods: Skin biopsies and peripheral blood at baseline (before therapy, 24weeks, 54 weeks) from 23 Ustekinumab patients with psoriasis who had ultrasound imaging confirmed subclinical enthesopathy) were recruited. Cellular immunophenotyping was performed using multi-parameter flow cytometry to detect tetherin on (Monocyte, B cells, T cells and neutrophils). All data was compared to age-matched samples from healthy controls (HC). Skin biopsies were digested and RNA extracted, qPCR of common ISGs genes were analysed in lesional and peri-lesional at corresponding time points. Results: Tetherin showed a higher level of expression on blood subsets of psoriasis compared to HC at baseline on Monocytes, T cells, NK cells and B cells (p=0.003, =0.005, =0.035, =0.002) compared to the baseline. No significant changes observed between baseline and 2nd visit 24 weeks. Interestingly, a substantial reduction in tetherin expression at (52 weeks) in psoriasis was observed in all subsets in Monocytes, T cells, NK cells and B cells (all p<0.0001) correlating with patient response to therapy. IFN signature by TaqMan revealed higher expression in skin biopsies distinctive ISGs compared to HC, e.g. IFI27, STAT1, IFI16 and IRF7 all corrected post-Ustekinumab therapy to normal levels. Paired analysis revealed a stronger IFN signature in lesional biopsies vs non-lesional biopsies, e.g. IFI27 (p=0.0312, Wilcoxon matched pair-rank test). Conclusions: Psoriasis which is genetically and mechanistically linked to IFN-I signatures shows responses to Ustekinumab therapy that correlate with improvement in IFN-I signatures in blood and tissues. Given that whole blood ISG signatures were complex and weakly correlating with disease activity. We provide a convenient, validated method to analyse IFN pathway in routine clinical practice using tetherin which could be a future research tool for the cell-specific IFN-I response. These studies support the idea that p40 efficacy in psoriasis is associated with IFN-I pathway modulation and relevant for exploring how p40 blockers may exert potential benefit in SLE. References: 1. Krueger, et al. N Engl J Med. 2007Feb 8;356(6):580–92. Disclosure of Interest: None declared